PERAN APLIKASI DIGITAL PADA KINERJA BISNIS KEDAI KOPI SKALA MIKRO DI DIY - Rogatianus Maryatmo; Devi Victoria Pamenta (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
This study aims to determine the relationship between the determinants of the use of digital applications on business performance. Determinants of the use of digital applications are measured using: the age of the business owner, the last education of the business owner, the experience of the business owner, business location, business size, application cost, technology literacy, government, and internet access speed. Meanwhile, business performance is measured using indicators: revenue, sales output, number of employees, and customers. The object of research is the micro-scale coffee shop businesses in the Province of DIY. Data is collected through structured questionnaires and distributed online using Google Forms. A total of 100 respondents were collected using the purposive sampling method. It is employed cross-tabulation and the chi-square test to process the data. The results showed that the speed of internet access relates to sales output, number of employees, and number of customers. Business size and government have a relationship with income. The age of the business owner relates to sales output. In contrast, other variables do not relate to each other. Keywords: business performance; digital application; coffee shop, Yogyakarta Penelitian ini bertujuan untuk mengetahui hubungan antara determinan penggunaan aplikasi digital terhadap kinerja bisnis. Determinan penggunaan aplikasi digital diukur dengan menggunakan: umur pemilik usaha, pendidikan terakhir pemilik usaha, pengalaman pemilik usaha, lokasi usaha, ukuran usaha, biaya aplikasi, literasi teknologi, pemerintah, dan kecepatan akses internet. Sedangkan kinerja bisnis diukur dengan pendapatan, output penjualan, jumlah karyawan, dan jumlah pelanggan. Objek penelitian adalah usaha kedai kopi skala mikro di Provinsi DIY. Data dikumpulkan melalui kuesioner terstruktur dan didistribusikan secara daring menggunakan Google Form. Sebanyak 100 responden berhasil dikumpulkan dengan menggunakan metoda sampel bertujuan. Data diolah dengan menggunakan alat analisis tabulasi silang dan uji kai kuadrat. Hasil penelitian menunjukkan bahwa kecepatan akses internet memiliki hubungan terhadap output penjualan, jumlah karyawan, dan jumlah pelanggan. Ukuran usaha dan pemerintah memiliki hubungan terhadap pendapatan. Umur pemilik usaha memiliki hubungan terhadap output penjualan. Sedangkan variabel lainnya tidak saling berhubungan. Kata Kunci: kinerja bisnis; aplikasi digital; usaha skala mikro; kedai kopi; Yogyakarta